Social impact analysis of urban riverfront regeneration; River of Life (RoL), Kuala Lumpur City Hall (KLCH) - Mohamed Osman, Mariana; Abdullah, Muhammad Faris; Asmawi, M. Zainora; Ramlan, Nuranisa Huda (e-International Publishing House, Limited, 2019)
The River of Life (ROL) is a riverfront regeneration project that aims to transform the Klang River into a vibrant waterfront with high economic value. The study aims to define the implications of the RoL towards society in the area of KLCH. One hundred fifty respondents of local and international visitors completed the survey. From the findings, it shows that the respondents reacted favorably to all of RoL's social consequences, but improvements from the aesthetic and awareness is needed. These results help to maximize economic growth, enhancing social interaction and environmental preservation, especially in the urban.